Is fascia iliaca compartment block or intravenous opioid analgesia better when positioning patients with fractured neck of femur for spinal anaesthesia?. (2nd February 2021) - Heard, R; Clements, P
Abstract : Patients with a fractured neck of femur require effective analgesia to improve positioning before the administration of spinal anaesthetic. This article discusses the evidence to show whether fascia iliaca compartment block or intravenous opioid analgesia is preferable in this situation.